Viral metagenomics updated the prevalence of human papillomavirus types in anogenital warts - Hui Xu; Yu Ling; Yuan Xi; Hong Ma; Hao Wang; Hui-Min Hu; Qi Liu; Yu-Mei Li; Xu-Tao Deng; Shi-Xing Yang; Eric Delwart; Wen Zhang (Emerging Microbes and Infections)
To investigate the composition of human papillomavirus (HPV) types in anogenital warts (AGWs), viral nucleic acid in 110 AGWs, pooled into 11 specimen pools, were subjected to viral metagenomic analysis. After finding HPV7 in AGWs, conventional PCR screening was performed for HPV7 in other 190 individual AGW specimens. Viral metagenomic results indicated that 29 different types of HPV were recovered, with HPV11 and HPV6 showing the highest proportion of sequence reads. HPV7 was detected in 7 of 11 pools, 5 of which contained abundant HPV7 sequence reads. 24 complete genomes of HPV were acquired in viral metagenomic analysis, including 5 HPV7 genomes, based on which phylogenetic analysis and pairwise sequence comparison were conducted. PCR screening for HPV7 in other 190 individual AGW specimens revealed 25 positive cases (13.16%), of which the amplified fragments were sequenced and confirmed to be HPV7 sequences. Although HPV7 was generally found in hand warts and recently also in warts in toe webs, our data suggested that the role of HPV7 in AGW should be considered in the future clinical test and vaccine development for AGWs.